A nationwide, multi‐institutional collaborative retrospective study of colorectal neuroendocrine tumors in Japan. Issue 2 (17th November 2020) - Yamaguchi, Tatsuro; Takahashi, Keiichi; Yamada, Kazutaka; Bando, Hiroyuki; Baba, Hideo; Ito, Masaaki; Funahashi, Kimihiko; Ueno, Hideki; Fujita, Shin; Hasegawa, Seiji; Sakai, Yoshiharu; Sugihara, Kenichi
Abstract: Aim: Neuroendocrine tumors (NETs) are one of the subtypes of neuroendocrine neoplasms and are defined as epithelial neoplasms with predominant neuroendocrine differentiation. The aim of this study was to clarify the clinicopathological characteristics of colorectal NETs through a nationwide retrospective study in Japan. Methods: This multicenter retrospective cohort study of NETs in Japan was conducted by the study group of the Japanese Society for Cancer of the Colon and Rectum. In this study, we aimed to clarify the characteristics of Japanese patients with colorectal NETs. This cohort study included patients with colorectal NETs who were treated from January 2011 to December 2015. Results: Most NETs developed in the lower rectum. Predictive factors of lymph node metastasis included size (>10 mm), depth of invasion (muscular propria or greater), NET grade (NET G2), depressed lesion of the tumor, and lymphovascular infiltration. In particular, depressed lesion of the tumor and lymphovascular infiltration were independent predictive factors of lymph node metastasis. The presence of an increased number of these predictive factors increased the lymph node metastasis rate. Conclusion: Surgical resection with lymph node dissection is considered in the colorectal NETs patients with predictive factors of lymph node metastasis, the number of which is correlated with incidence of lymph node metastasis. Abstract : This Japanese multicenter retrospective study revealed clinicopathological characteristics and the risk factors of lymph node metastasis in colorectal neuroendocrine tumors.